Resilience and social support as protective factors against abuse of patients with dementia: A study on family caregivers. (24th May 2018) - Serra, Lídia; Contador, Israel; Fernández‐Calvo, Bernardino; Ruisoto, Pablo; Jenaro, Cristina; Flores, Noelia; Ramos, Francisco; Rivera‐Navarro, Jesús
Abstract : Objective: Scientific literature has identified different vulnerability factors associated to abuse in people with dementia (PWD), but little is known about the psychosocial protective variables against abuse. The main objective of this study is to investigate a set of caregiver and patient factors linked to abuse‐related behavior of PWD. Methods: A total of 326 primary and family caregivers, residents of the Castilla and León community (Spain), were evaluated. All participants filled out a standardized protocol, which assessed the sociodemographic characteristics, patient and care‐related variables, as well as the perceived burden, resilience, and social support. Abuse‐related behavior was evaluated using the Caregiver Abuse Screen. Results: Results show that the severity of cognitive impairment and behavior disorders of PWD, a greater number of caregiving hours, a worse previous relationship with the caregiver, and perceived burden are positively related with abuse. However, resilience and social support showed a negative relationship with Caregiver Abuse Screen scores, suggesting a protective effect on abuse, even after controlling the effect of a number of covariates. Indeed, resilience was the only variable that remained significant after including the effect of burden. Conclusions: This paper states the role of burden in abuse of PWD, while resilience and social support are abuse protective factors. These variables should be considered in future guidelines for the prevention of abuse against PWD.